Juridical Analysis of Non-Profit Principles in The Formation of Business Entities by Foundations - Mustofa Muhammad Haris (Yayasan Tranformasi Aksara Digital, 2024)
The establishment of non-profit organizations such as foundations aims to support social, religious, and humanitarian causes. However, the operational flexibility provided by Law Number 16 Year 2001 on Foundation, as amended by Law Number 28 Year 2004, allows foundations to establish business entities to generate income. This research examines the application of the non-profit principle in the establishment of business entities by foundations, emphasizing the balance between its charitable and commercial functions. Using normative legal research with a socio-legal approach, this study analyzes primary and secondary legal materials to evaluate compliance with the non-profit principle and governance practices. The results show that although the flexibility of establishing a business entity supports the sustainability of the foundation, strict governance, transparency, and accountability are required to prevent misuse of resources. The research concludes that the application of the non-profit principle is important to maintain public trust and ensure the foundation remains true to its mission. The research also highlights the urgency of strengthening the regulatory framework and oversight mechanisms.